2004
DOI: 10.1074/jbc.m408354200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Analyses of Two New Calcium-activated Chloride Channel Family Members from Mouse Eye and Intestine

Abstract: Two new calcium-activated chloride channel (CLCA) family members, mCLCA5 and mCLCA6, have been cloned from mouse eye and intestine, respectively. mCLCA5 is highly homologous to hCLCA2, and mCLCA6 is highly homologous to hCLCA4. mCLCA5 is widely expressed with strong expression in eye and spleen, whereas mCLCA6 is primarily expressed in intestine and stomach. mCLCA6 is also expressed as a splice variant lacking exon 8 and part of exon 10 in intestine and stomach. Transfection of tsA201 cells with enhanced green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
70
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 42 publications
8
70
0
Order By: Relevance
“…Homologs were subsequently identified in other species, with at least six in mouse and four in human (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). With the sequencing of numerous genomes, it has become apparent that CLCA proteins are found throughout the chordates and possibly in some invertebrates (13).…”
mentioning
confidence: 99%
“…Homologs were subsequently identified in other species, with at least six in mouse and four in human (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). With the sequencing of numerous genomes, it has become apparent that CLCA proteins are found throughout the chordates and possibly in some invertebrates (13).…”
mentioning
confidence: 99%
“…Both proteins are thought to be expressed in the intestine (Agnel et al 1999;Evans et al 2004), and the hCLCA1/hCLCA4 gene locus has been shown to play a role as modulator of the basic intestinal chloride secretory defect in CF (Ritzka et al 2004). However, the cell type expressing these proteins and their subcellular location are as yet unknown.…”
mentioning
confidence: 99%
“…Murine mCLCA6 has recently been discovered as the murine ortholog of human hCLCA4 (Evans et al 2004). Both proteins are thought to be expressed in the intestine (Agnel et al 1999;Evans et al 2004), and the hCLCA1/hCLCA4 gene locus has been shown to play a role as modulator of the basic intestinal chloride secretory defect in CF (Ritzka et al 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Six members of this family have been identified, cloned and partially characterized in the mouse: Clca1 (Gandhi et al 1998, Romio et al 1999, Clca2 (Lee et al 1999), Clca3 (Komiya et al 1999), Clca4 (Elble et al 2002), Clca5 and Clca6 (Abdel-Ghany et al 2003, Beckley et al 2004, Evans et al 2004. Structural analysis indicates significant similarities among different CLCA family members, including protein sizes of 902-943 amino acids and four or five transmembrane regions (Pauli et al 2000, Jentsch et al 2002.…”
Section: Introductionmentioning
confidence: 99%